The Effect Of Firm Size, Profitability, and Capital Structure On Firm Value: PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Wahyuningtyas, Sanggita (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
This research aims to examine the effect of firm size, profitability and capital structure to firm value in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange. This study uses the object of research as many as 22 companies listed on the Indonesia Stock Exchange. Samples were taken by purposive sampling method and met the sample selection criteria. The statistical method uses Multiple Linear Regression analysis. The test results show that simultaneously the independent variables consisting of firm size, profitability and capital structure have a significant effect on firm value. While partially the variables of firm size and profitability have a positive and significant effect on firm value, while capital structure has no significant effect on firm value.